2021
DOI: 10.1002/pc.25944
|View full text |Cite
|
Sign up to set email alerts
|

A new study on flax‐basalt‐carbon fiber reinforced epoxy/bioepoxy hybrid composites

Abstract: The present research investigation focuses on the development of flax-basaltcarbon fiber reinforced epoxy/bioepoxy hybrid composites under different stacking sequence technique. The composites were fabricated using manual hand lay-up method and compression molding technique. The specimens were prepared using standard ASTM methods and subjected to various mechanical experimentations such as tensile, flexural, interlaminar shear strength, and impact tests. Water absorption study under distilled water condition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 67 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The hybridization of kenaf/pineapple was reported to increase the mechanical and water absorption resistance of polypropylene hybrid composites by N. L. Feng et al. [19] P. Madhu et al [20] and T. G. Y. Gowda et al [21] concluded that the evaluated mechanical properties were significantly increased for hybridization of Prosopis juliflora-glass-carbon and flax-basalt-carbon fiber reinforced polymer composites. Caryota urens natural fiber and glass fiber reinforced nanoclay/SiC toughened epoxy nanocomposite were reported to exhibit excellent mechanical and wear properties by P. Raju et al.…”
Section: Introductionmentioning
confidence: 99%
“…The hybridization of kenaf/pineapple was reported to increase the mechanical and water absorption resistance of polypropylene hybrid composites by N. L. Feng et al. [19] P. Madhu et al [20] and T. G. Y. Gowda et al [21] concluded that the evaluated mechanical properties were significantly increased for hybridization of Prosopis juliflora-glass-carbon and flax-basalt-carbon fiber reinforced polymer composites. Caryota urens natural fiber and glass fiber reinforced nanoclay/SiC toughened epoxy nanocomposite were reported to exhibit excellent mechanical and wear properties by P. Raju et al.…”
Section: Introductionmentioning
confidence: 99%
“…[26,27] The incorporation of single fiber reinforcement of natural fibers causes non-homogenous distribution in the matrix; this causes deformations in the combinations and thus reducing the mechanical properties. [28][29][30] The combination of 10 wt% R/10 wt% K/3 wt% of T (Figure 8C) observed improved tensile properties due to the hybridization of both ramie and kenaf fibers; this created much more even distribution of fibers in the matrix region with improved properties. [31] The optimized combination with 10 wt% R/10 wt% K/5 wt% of T (Figure 8D) from GRA and TOPSIS method observed good properties mainly due to the reduction in hydrophilic nature of the combination by the benzoyl chloride surface treatment at 5 wt%.…”
Section: Morphological Analysis Of the Tested Specimenmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27] Natural filler-based polymer composites are becoming more common in a variety of applications, including construction and building, locomotives, furniture, and the packaging industry. [28][29][30][31][32][33] HB leaf fillers were (5,15, and 25 wt%) blended with high-density poly ethylene (HDPE). The best properties of the composite were found at 5 wt% of HDPE/Hevea brasiliensis Leaf (HBL) and it was revealed the maximum impact strength of 9.889 kJ/m.…”
Section: Introductionmentioning
confidence: 99%